1993
DOI: 10.1007/bf01316896
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus specific porcine cytotoxic T cell activity

Abstract: African swine fever virus (ASFV) specific, cytotoxic T lymphocyte (CTL) activity has been studied in a protection model in which SLA inbred miniature swine are experimentally inoculated with a naturally occurring, non-fatal ASFV isolate (NHV). Peripheral blood mononuclear cells (PBMC) from such infected swine show significant activity in CTL assays, using cultured ASFV-infected porcine blood derived macrophages as target cells. This CTL activity is elicited from PBMC by in vitro restimulation of effector cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 26 publications
(23 reference statements)
3
50
0
2
Order By: Relevance
“…The exclusive lysis of autologous but not of heterologous target cells as well as the blocking of virus specific lysis by monoclonal antibodies against CD8 or MHC class I antigen indicated that the recognition of virus-infected targets by CSFV-specific CTL is a classical MHC class Irestricted process. Although inhibition with MAb 2.27.3a (anti-MHC class I) was only partial, the result is consistent with previously described inhibition of CTL activity in other studies (Martins et al, 1993). The virusspecific CTL described here belong to the CD4-CD6+CD8 + T lymphocyte subpopulation as demonstrated in chromium release assays with separated effector cell populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The exclusive lysis of autologous but not of heterologous target cells as well as the blocking of virus specific lysis by monoclonal antibodies against CD8 or MHC class I antigen indicated that the recognition of virus-infected targets by CSFV-specific CTL is a classical MHC class Irestricted process. Although inhibition with MAb 2.27.3a (anti-MHC class I) was only partial, the result is consistent with previously described inhibition of CTL activity in other studies (Martins et al, 1993). The virusspecific CTL described here belong to the CD4-CD6+CD8 + T lymphocyte subpopulation as demonstrated in chromium release assays with separated effector cell populations.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore antigen presentation to CD4 + T lymphocytes does not occur under these conditions. Interestingly, the effector cells showed a high nonspecific lysis of non-infected target cells which has been previously described in conjunction with other viral infections of swine (Martins et al, 1993). This nonspecific lysis may be due to either non-specific activity of the effector cells or lymphokine-activated killer cells (LAK).…”
Section: Discussionmentioning
confidence: 56%
“…Specific identification of the various subpopulations of leukocytes enables improved investigations of the immune response to various porcine infections such as Actinobacillus pleuropneumoniae, African swine fever virus, classical swine fever virus, porcine reproductive and respiratory syndrome virus (PRRSV) and Aujeszky disease virus [6, 41,76,110,116,127,137,213]. An understanding of these interactions is essential for the development of new generations of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some instances where neutralizing antibodies were not detectable, a relative protection was observed suggesting a possible protective role for T cells [21]. Cellular immune responses, especially virus-specific cytotoxic T lymphocytes (CTL), have been shown to represent an important defense mechanism against African Swine Fever Virus (ASFV) infection in pigs [13]. These mechanisms have also been demonstrated for the Pestiviruses bovine viral diarrhea virus [3] and border disease virus [34].…”
Section: Introductionmentioning
confidence: 99%